Quantum Efficiency Enhancement Depending on the Thickness of p-GaN Spacer Layer in Localized Surface Plasmon-Enhanced Near-Ultraviolet Light-Emitting Diodes by Using Colloidal Silver Nanoparticles. (20th August 2019) - Hong, Sang-Hyun; Kim, Na-Yeong; Kang, Jang-Won; Kim, Jae-Joon; Jung, Yen-Sook; Kim, Dong-Yu; Yim, Sang-Youp; Park, Seong-Ju
Abstract : We demonstrated the dependence on thickness of p-GaN spacer layer in the localized surface plasmons (LSPs)-enhanced near-ultraviolet light-emitting diodes (NUV-LEDs) by pneumatic spray process using colloidal silver (Ag) nanoparticles (NPs). The LSPs-enhanced NUV-LEDs with 10- and 20-nm-thick p-GaN spacer layer showed enhanced internal quantum efficiency (IQE) and reduced effective exciton lifetime by introducing the colloidal Ag NPs. The IQE of LSPs-enhanced NUV-LEDs with 10- and 20-nm-thick p-GaN spacer layer was increased by 18.8% and 24.2%, respectively. These results indicate that the spontaneous emission rate is increased by LSPs-excitons resonant coupling. However, the NUV-LEDs with 40- and 100-nm-thick p-GaN spacer layer showed decreased IQE and extended exciton lifetime due to the evanescent wave property of LSPs field from colloidal Ag NPs.